Methodology in the cassava on-farm trials: An interim evaluation - Lynam, John K. (International Center for Tropical Agriculture, 1982)
The different methodological stages of cassava on-farm trials and their relationships regarding the objectives and functions of the Cassava Program at the Centro Internacional de Agricultura Tropical (CIAT) are outlined. Site selection, farm trial design and analysis, and some illustrative results are included. Trials are currently focussed on: (1) comprehension of the factors determining yields in traditional cassava production systems; (2) determination of the changes in the systems necessary to support the higher yield plateau of the hybrid var.; and (3) determination of the changes necessary to adapt these systems to the requirements of new industrial markets. The need for clear objectives in this type of program is emphasized. On the other hand, the design of methodology will depend on the particular stage of development of the research program and the particular characteristics of the crop or cropping system. From these initial trials it was concluded that yield and quality variation was much greater between farms than between treatments, thus orientating methodology towards working with substantial variation in the yield estimates. On-farm trialswill eventually evolve as a tool for ex-ante evaluation of integrated cassava production and market development projects. Tables on the types of variables used and the results obtained in trials carried out in Colombia are included. (CIAT)